Strategi Pemasaran Jasa pada Perguruan Tinggi - Juliana, Juliana; Qatrunnada Jinan Akmaliah; Umi Kalsum; Mahfudz Ifendi (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Universities face increasingly fierce competition in attracting new students amidst changes in technology and societal preferences. An effective service marketing strategy is the key to increasing competitiveness and maintaining the existence of higher education institutions. This research aims to identify relevant marketing strategies, analyze their success factors, and provide recommendations based on a literature review. Data was collected from various literature sources that discuss the main elements of service marketing, such as branding, digital marketing, and service quality, using content analysis methods. The research results show that appropriate market segmentation, customer relationship management (CRM), and the use of digital technology, such as social media and data-based marketing, are the main factors in increasing the attractiveness of higher education. Additionally, a strong branding strategy and improving service quality play an important role in building reputation and creating a positive experience for students. These findings underline the importance of marketing innovation integrated with technology and improving academic and non-academic services to strengthen institutional competitiveness in an increasingly dynamic higher education market.